Cultivating Digital Media Ethics Awareness: The Dangers of Deepfakes and Disinformation for Teenagers (MTSS AL-Hidayah) - hidayat, andrian; Napila, Ade (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Deepfakes are fake digital content (images, videos, or audio) that are realistically synthesized using artificial intelligence (AI) and machine learning techniques, such as artificial neural networks. This technology is capable of manipulating media, for example by swapping faces or forging voices, creating the illusion that a person has performed actions they never actually did. In Indonesia, deepfake has evolved from an entertainment tool into a serious threat, causing various cases involving the general public, public figures, and stakeholders. Given the high risk, understanding the identification and response to deepfake content needs to be instilled early on, especially among adolescents, to minimize negative impacts in the digital era. This Community Service (Pengabdian Kepada Masyarakat/PKM) activity aims to increase the knowledge and awareness of Madrasah Tsanawiyah (MTs) students regarding the deepfake phenomenon and its impact on daily digital security. The PKM implementation uses educational methods through structured counseling, interactive discussions, and simple practices for detecting the characteristics of deepfake content. The results of the activity show a significant increase in students' knowledge and critical attitude towards digital security issues. Students now have the basic foundation to detect manipulative content, making them more vigilant and selective in filtering information circulating on social media. Keywords: Deepfake, Digital Security, Adolescents, Community Service.